2021
DOI: 10.14238/pi61.3.2021.133-40
|View full text |Cite
|
Sign up to set email alerts
|

External risk factors associated with language disorders in children

Abstract: Background Children with language delay have deficits in the ability to learn and use language, either expressive and/or receptive despite otherwise normal development. Language delay could be influenced by either internal factors (within the child) and external factors (from the environment). Timely identification and modification of these risk factors can allow early intervention to reduce child disability and are associated with better long-term outcomes. Objective To identify possible risk factors re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In Indonesia, the prevalence of children with language difficulties and disorders is quite high. Based on data from Dr. Cipto Mangunkusumo hospital in 2006, it was found that 10.13% of pediatric rehabilitation patients received a diagnosis of language disorder (Wangke et al, 2021). Another study related to developmental challenges in speech, language and communication in Indonesia found that 55.6% of preschool-aged children experienced difficulties in at least one of the five areas of speech and language (Hapsari, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Indonesia, the prevalence of children with language difficulties and disorders is quite high. Based on data from Dr. Cipto Mangunkusumo hospital in 2006, it was found that 10.13% of pediatric rehabilitation patients received a diagnosis of language disorder (Wangke et al, 2021). Another study related to developmental challenges in speech, language and communication in Indonesia found that 55.6% of preschool-aged children experienced difficulties in at least one of the five areas of speech and language (Hapsari, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Providing positive stimulation by talking and telling stories can also promote language development in children (Dunlap, 2009). Other studies found that shared story reading sessions can be associated with a reduced risk of language difficulties (Wangke et al, 2021). By reading stories to preschool-aged children, parents can facilitate children's verbal language development (Towson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations